STRUKTUR ANATOMI ENAM JENIS KAYU ASAL PAPUA - Andianto Andianto; Raden Esa Pangersa Gusti (Jurnal Penelitian Hasil Hutan, 2016)
Anatomical properties is necessary for wood species identification. This paper observes anatomical properties of six wood species originated from Papua. Wood species studied include: ketapang  (Terminalia complanata K. Schum.); pala hutan (Gymnacranthera paniculata (A.DC.) Warb.); bipa (Pterygota horsfieldii (R.Br.) Kosterm).; kelumpang (Sterculia shillinglawii F. Muell.); manggis/kandis (Pentaphalangium parviflorum); and lancat/lebani (Mastixiodendron pachyclados (K. Schum) Melch.). Anatomical properties were observed according to IAWA (International Association of  Wood Anatomists) checklist. The anatomical main properties observed in ketapang wood were vestured pits, prismatic crystals in non-chambered axial parenchyma cells, and druses. Pala hutan main anatomical properties were the presence of tannin tubes and oil cells which were associated with axial parenchyma. Prismatic crystals in axial parenchyma cells, and rays of two distinct sizes were two main anatomical characteristics of bipa and kelumpang wood. Prismatic crystals in chambered axial parenchyma cells was one of characteristics of manggis wood. Vestured pits and scanty paratracheal parenchyma were two main characteristics of lancat wood. For identification pur poses, bipa wood could be distinguished by banded parenchyma; polygonal alternate pits; and prismatic crystals in non- chambered axial parenchyma cells.